(3HdhZ GdbQi aj Pjd GJMGa GdhQi HCNHGQ Ce GdbQis - (3YHO GdYRjR Hf YeQ Hf eMeO, YR GdOjf , CHh GdNjQ , GdTgjQ HGHf agO,J (B920 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd CNHGQ GdfGS eQCI ddfGXQjf CeG HYO aEf Yde GdJGQjN Ldjd GdahGjO cKjQ GdUdI hGdahGjO GP Hg jYQa CMhGd GdChdjf hGdBNQjf s
(3BNQgG (B:s
(3jfJgi HGNHGQ SfI (B922 (3Hbhdg (B: (3Cgd LeGO GdChd djdI GdKdGKGA SfI (B922 (3ai jhe GdLeYI QGHY GdTgQ hUd ecI bGadI GdeOjfI GdTQjaI s
(3HgG fXGe GdJYbjHIs
(3fbdJ Yf fSNI HNW GdeDdas
(3QHeG jchf GdfGSN gh CMeO HfeUWai cJfLi s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs